FOR WHAT PURPOSE DO THE STUDENT TEACHERS USE DGS? A QUALITATIVE STUDY ON THE CASE OF CONTINUITY - Bülbül, Buket Özüm; Güler, Mustafa; Gürsoy, Kadir; Güven, Bülent (International Online Journal of Education and Teaching, 2020)
Although numerous studies have investigated how technology affects academic achievement, very few have focused on the purpose of the use of technology in mathematics education. This current study examines how student teachers (STs) benefit from GeoGebra as one of the Dynamic Geometry Software (DGS) while solving continuity problems. In order to have deeper insights and a better understanding of the intended purposes, a case study research design was adopted for this study. Participants in the study were seven mathematics STs. Six open-ended problems were used to collect data. Three themes were found to be relevant for understanding how STs use DGS in a problem solving process: visualize, verify, and calculate. The paper also shows the potential misconceptions of the STs. Keywords: Dynamic Geometry Software, GeoGebra, problem solving, aim of use, continuity